SAN: an Integrated Unmanned Air Vehicles Interdictor System Concept - Marcin KRÓL (Koncepcja Zintegrowanego Systemu Antydronowego – SAN, 2017)
he development of unmanned air vehicles (UAVs) has been very rapid recently. The wide accessibility of UAVs has unlocked a great potential for the malicious or accidental damage or destruction of property or other aircraft in flight. UAVs can be used for espionage, contraband, and the trafficking or transport of arms and hazardous materials. Every month sees a growing number of reports of incidents that involve remote-controlled UAVs operated for aerial video recording. These incidents justify undertaking research into minimizing the hazards which UAVs may potentially cause. A concept was developed for a solution dedicated to this problem and comprising an integrated modular anti-UAV system for application in commercial (civilian) markets in the areas of security of mass events, strategic enterprises, and critical strategic infrastructure in Poland. The proposed system is intended to incapacitate any UAVs that breach a predefined air space and bring the incapacitated UAVs safely to the ground. The project is developed jointly by the Institute of Armament Technology at the Military University of Technology (Warsaw, Poland) and Polish company Ellipsis Sp. z o.o.
Keywords: System antydronowy